Penerapan Metode Multiple Discriminant Analysis untuk Mengukur Tingkat Kesehatan yang Mengindikasikan Gejala Financial Distress pada Bank Umum Syariah - Nada, Shofaun (Faculty of Shariah and Law, 2013)
This research aims to account, analyse, and compare the level of Islamic commercial banks health using CAMELS method mentioned in PBI No. 9/1/PBI/2007 and SEBI No. 9/24/DPBs/2007, and using multiple discriminant analysis (MDA) altman z-score method. There are only four from six factors that used in CAMELS: capital, asset, earning, and liquidity excluding management and sensivity of market risk factor. The variables of capital factors are KPMM and ECR ratio. Asset factor consist of KAP and NPF ratio. Earning factor contains four ratios, such as NOM, ROA, ROE, and REO.DOI: 10.15408/aiq.v5i2.2119